On defence expenditure reduction: Balancing between austerity and security in Greece - Andreou, Andreas S.; Zombanakis, George A.; Migiakis, Petros M. (My University, 2013)
This paper aims at contributing a literature update by assessing the impact of policies focusing on defence-procurement spending on the growth rate of the Greek economy with special reference to the recent crisis environment using artificial neural networks. The main conclusion drawn in the case of the Greek economy in general and during austerity times in particular, is that defence-procurement policy is considerably inflexible concerning both increases and reductions. In fact any further decreases will have a direct impact on the security of the country given the dramatic reduction of the defence budget and the arms race against Turkey. By contrast, any increases will only burden the balance of payments without adding to the GDP, once the bulk of the defence equipment is imported due to the inefficiency of the domestic defence industrial base. A compromise, therefore, between security and austerity would call for a gradual shift towards domestic sources procurement, assuming, of course, considerable upgrading of the Hellenic defence industrial base.
Keywords: Debt; Defence expenditure; Economic growth